Generic key to chilean jumping plant-lice (Homoptera: Psilloidea) with inclusion of potential exotic pests - Burckhardt, D.
(Es, En)
Ilus., 31 ref.
Keywords: PSILA; HOMOPTERA; PSILIDAE; ESPECIES NUEVAS; IDENTIFICACION; CHILE; REVISTA CHILENA DE ENTOMOLOGIA